The First Map of Slovenia - Falski, Maciej (Poznańskie Studia Slawistyczne, 2017)
The first map of Slovenia was published only in 1861; it was the work of Peter Kozler, Slovenian lawyer and self-taught cartographer. If we analyze it in context of contemporary cartography, its novelty appears clearly. Kozler’s map was based on the principle of ethnicity, and not on a historical and juridical tradition of the Habsburg lands as it was the usage. The border of Slovenian territory crossed historical provinces. The map is presented in the paper as a visual realization of the principles of United Slovenia (Zedinjena Slovenija), first Slovenian political movement in 1848, which claimed unity and autonomy of the Slovenian nation. The performative and constructivist character of the document is strengthened, as far as it didn’t describe an existing state of matters, but was rather postulating a non-existing yet political entity of Slovenes. Thus, the form and function of the map, on the example of Kozler’s one, seem support a political idea of Slovenian national emancipation.